2016
DOI: 10.22436/jnsa.009.06.23
|View full text |Cite
|
Sign up to set email alerts
|

Approximations for Burgers equations with C-N scheme and RBF collocation methods

Abstract: The Burgers' equation is one of the typical nonlinear evolutionary partial differential equations. In this paper, a mesh-free method is proposed to solve the Burgers' equation using the finite difference and collocation methods. With the temporal discretization of the equation using C-N scheme, the solution is approximated spatially by Radial Basis Function (RBF). The numerical results of two different examples indicate the high accuracy and flexibility of the presented method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…and ζ n can be computed from Equation (15). One can write Equations (5), (17), (18) and boundary conditions (2) in the matrix form as follows…”
Section: Lie-group Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…and ζ n can be computed from Equation (15). One can write Equations (5), (17), (18) and boundary conditions (2) in the matrix form as follows…”
Section: Lie-group Methodsmentioning
confidence: 99%
“…Bouhamidi et al [17] presented RBFs interpolation technique for spatial discretization and implicit Runge-Kutta (IRK) schemes for temporal discretization of the unsteady coupled Burgers'-type equations. Xie et al [18] approximated the solution of the Burgers' equation spatially by the multiquadric MQ-RBF and used C-N finite difference scheme as temporal discretization technique.…”
Section: Introductionmentioning
confidence: 99%
“…A comparison with the method of Mittal and Jain 57 at different times is shown in Table 7, for x ∈ [0.5, 1.5] and ∈ {0.002, 0.000666666}. A further comparison with the mesh-free method of Xie et al 61 at different times is shown in Table 8, for x ∈ [ −3, 3] and = 0.0001. Figure B shows the approximate solution on the same region obtained using N = 12, for the parameters = 0.002, and = −0.4.…”
Section: Tablementioning
confidence: 99%
“…Sarboland and Aminataei (2014) presented two meshfree methods for solving the one-dimensional nonlinear non-homogeneous Burgers' equation using the MQ quasi-interpolation operator and direct and indirect radial basis function network schemes. Xie et al (2016) suggested a meshfree scheme by utilizing the finite difference and the MQ-RBF method, for solving the Burgers' equation numerically. Seydaoglu et al (2016) obtained the numerical solutions of Burgers' equation using highorder splitting methods combined with spectral methods, finite difference, and Weighted Essentially Nonoscillatory (WENO) schemes.…”
Section: Introductionmentioning
confidence: 99%